A broadband DC to 20 GHz 3-bit MEMS digital attenuator. (5th April 2016) - Sun, Junfeng; Zhu, Jian; Jiang, Lili; Yu, Yuanwei; Li, Zhiqun
Abstract: A 3-bit microelectromechanical system (MEMS) digital attenuator is designed with 0–20 GHz bandwidth. The attenuation ranges from 0 to 35 dB with 5 dB step. The attenuator, with the coplanar waveguide (CPW), is implemented by surface sacrificial layer technology. The DC-contact MEMS switches with three contact dimples are symmetrically placed around the T type resistor network, making the switches minimum in number and the structure compact. Through the lumped parameter method, the attenuator has good terminal matches in different attenuation states. The test results show that eight different attenuation states are realized within 0–20 GHz. The attenuation deviation is less than ±5%, the insertion loss is less than 1.7 dB and the voltage standing wave rations is less than 1.4 under most of the attenuation states. With the MEMS switches and CPW being adopted, the attenuator has the advantages of higher linearity, lower insertion loss and power consumption. The chip size is about 3.2 mm 2 including the pad.